(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Tidal current can identify the current movement that comes generally (1 January 2020–9 February 2020) with generated force wind and tides data. Hydrodynamic simulation gave a result of a current speed of 0.30 m/sec until 0.87 m/sec in low tide conditions and 0.73 m/sec until 1.05 m/sec in high tide conditions. The current speed maximum is found in the river estuary area, and the minimum is in Badung Strait. Current speed in lower conditions is smaller than at high tides. With the sediment model, transport simulation can identify the position of sediment distribution in the Badung Strait. A lot of sediment resides in Gunaksa Coastal, and it moves to the south part of the Sanur area (in this area, deposition of sediment happens).Data from the current model and the sediment transport model can be used by the government as input data to address the influences of coastal erosion.